Enzymatic pitch control in the kraft pulping and bleaching of Eucalyptus spp. - Scheepers, Gerhardus C. (Gerhardus Coenraad) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.